Agriculture and climate change: An agenda for negotiation in Copenhagen - Nelson, Gerald C. (International Food Policy Research Institute, 2009)
Agriculture and climate change are inextricably linked. Agriculture is part of the climate change problem, contributing about 13.5 percent of annual greenhouse gas (GHG) emissions (with forestry contributing an additional 19 percent), compared with 13.1 percent from transportation. Agriculture is, however, also part of the solution, offering promising opportunities for mitigating GHG emissions through carbon sequestration, soil and land use management, and biomass production. Climate change threatens agricultural production through higher and more variable temperatures, changes in precipitation patterns, and increased occurrences of extreme events such as droughts and floods. And if agriculture is not included, or not well included, in the international climate change negotiations leading up to the 15th Conference of Parties (COP15) of the UN Framework Convention on Climate Change in Copenhagen in December 2009, resulting climate change policies could threaten poor farming communities and smallholders in many developing countries. The policies could also impede the ability of smallholders to partake in new economic opportunities that might arise from the negotiations.